Ctesias and his Eunuchs: a Challenge for Modern Historians - Lenfant, Dominique (Histos, 2012)
The prominence of eunuchs in Ctesias’ account of Persia has given rise in the last decades to a paradoxical combination of skepticism about their historicity and realistic interpretation questioning whether they were in fact castrated. The present paper brings to light the difficulties of the assessment of them as historical figures. It first takes into account the fact that we know Ctesias’ eunuchs only through fragments, that is, through the filter of later authors who refer to him while possibly having a personal relationship to eunuchs in their own society. It then describes the distinctive features of Ctesias’ eunuchs within Greek literature on Persia and presents the main interpretative trends on them. It examines possible touchstones and shows how difficult it is to cross-check Ctesias’ account of eunuchs with Near Eastern evidence. It assesses the foundations of current prevailing positions and shows that a hypothesis has become a—questionable—dogma on two sorts of historical referents for Ctesias’ εὐνοῦχοι. Lastly, it questions the pertinence of ‘orientalism’ as a label for the representation of eunuchs in Ctesias’ account and even highlights its shortcomings. All in all, this issue is, in fact, a perfect illustration of the methodological problems that modern historians often have to face when they try to study ancient Persia through the accounts of Greek historians.